Indicadores de qualidade do solo em sistemas agroecológicos no Cerrado Mineiro - Rocha, Ana Flávia Brandão (2021)
Soil quality is its ability to function within the limits of ecosystem and land use to ensure biological productivity, preserve environmental quality, and promote plant and animal health. Thus, the objective of this work was to select soil quality indicators sensitive to different agricultural practices adopted in areas of agroecological systems in the Cerrado Mineiro region. Soil samples were collected in the 0 to 20 cm layer, at the end of the dry season, in three different rural properties dedicated to an agroecological system (AS) located in the municipalities of Romaria and Uberlândia, Minas Gerais, Brazil. Ten soil samples were evaluated, five areas with agroecological management and five pasture areas as reference. Chemical attributes, microbiota population, microbial biomass carbon (MBC), basal soil respiration (BSR), and activity of beta-glucosidase, phosphatase, and arylsulfatase enzymes were evaluated. The variables basal respiration, beta-glucosidase, pH, bacterial, and actinobacteria colonies were sensitive to different agroecological (AS) and pasture management, thus these variables can be used as indicators of soil quality. The mean values between the ratio of AS and pasture of these indicators were 1.69, 1.20, 3.57 and 2.44, respectively. The agroecological cultivation areas presented a better- quality soil and, possibly, greater activity of its basic functions.